Arranjos produtivos locais: uma análise baseada na participação das organizações locais para o desenvolvimento - Tizziotti, Catarine Palmieri Pitangui; Truzzi, Oswaldo Mário Serra; Barbosa, Agnaldo De Sousa (Universidade Federal de São Carlos, 2019)
Abstract The approach of the New Sociological Institutionalism emphasizes the importance of culture, myths, and ceremonies in the institutional environment, and argues that institutions influence not only in the strategies of individuals but also in their identities. This approach is used in this study to understand why footwear’s local productive arrangement (LPA) in Franca organizations adopt and diffuse certain practices that bring, as a consequence of the defect in organizational relationships of this arrangement. For this, field research was conducted through semi-structured interviews with companies, professional associations and representatives of local government in footwear’s LPA in Franca.

Resumo A abordagem do novo institucionalismo sociológico destaca a importância da cultura, dos mitos e das cerimônias no ambiente institucional, bem como argumenta que as instituições influenciam não apenas as estratégias dos indivíduos, mas também suas identidades. Essa abordagem é utilizada neste estudo para entender por que o arranjo produtivo local (APL) de calçados das organizações de Franca, São Paulo, adota e difunde certas práticas que trazem como consequência a fragilidade nas relações organizacionais desse arranjo. Para isso, foi realizada uma pesquisa de campo por meio de entrevistas semiestruturadas com empresas, associações profissionais e representantes do governo local do APL de calçados de Franca.
Local productive arrangements: an analysis based on the participation of local organizations for development
Keywords: Institutional environment; Local production; Footwear industry; Franca-SP; Ambiente Institucional; Produção local; Indústria de calçados; Franca-SP